2016
DOI: 10.1038/srep39246
|View full text |Cite
|
Sign up to set email alerts
|

Overexcited MaxiK and KATP channels underlie obstructive jaundice-induced vasoconstrictor hyporeactivity of arterial smooth muscle

Abstract: Substantial evidence has shown that obstructive jaundice can induce vascular hyporesponsiveness. The present study was designed to investigate mechanisms of MaxiK channel and KATP underlying cholestasis-induced vascular dysfunction. The isolated thoracic aorta was used to explore norepinephrine (NE)-induced contraction. The function of MaxiK and KATP channels were investigated using whole-cell patch clamp recording. Compared with Sham group, NE-induced vascular contraction was blunted after bile duct ligation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It has been reported that BDL-induced cirrhosis alters the expression level of ion channels such as voltage-dependent Na + channels ( Lee et al, 2016 ), epithelial Na + channels ( Kim et al, 2006 ), large-conductance K Ca (BK Ca ) channels ( Yuan et al, 2016 ; Jadeja et al, 2017 ), ATP-sensitive K + channels ( Yuan et al, 2016 ), transient receptor potential canonical subfamily (TRPC) channels ( Nedungadi and Cunningham, 2014 ; Jadeja et al, 2017 ), and transient receptor potential vanilloid subfamily (TRPV) channels ( Nedungadi et al, 2012 ; Belghiti et al, 2013 ; Hong-Qian Wang et al, 2019 ). In addition, we noted the downregulation of TMEM16A (and also TMEM16F) expression in cirrhotic BDL mice, but not in non-cirrhotic PPVL mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BDL-induced cirrhosis alters the expression level of ion channels such as voltage-dependent Na + channels ( Lee et al, 2016 ), epithelial Na + channels ( Kim et al, 2006 ), large-conductance K Ca (BK Ca ) channels ( Yuan et al, 2016 ; Jadeja et al, 2017 ), ATP-sensitive K + channels ( Yuan et al, 2016 ), transient receptor potential canonical subfamily (TRPC) channels ( Nedungadi and Cunningham, 2014 ; Jadeja et al, 2017 ), and transient receptor potential vanilloid subfamily (TRPV) channels ( Nedungadi et al, 2012 ; Belghiti et al, 2013 ; Hong-Qian Wang et al, 2019 ). In addition, we noted the downregulation of TMEM16A (and also TMEM16F) expression in cirrhotic BDL mice, but not in non-cirrhotic PPVL mice.…”
Section: Discussionmentioning
confidence: 99%
“…The agonist activity on the bile acid receptors may represent a link between gut microbiota and the cardiovascular system (169). In addition to the dose-dependent vasorelaxation, bile acids also modulate the transcription of vasoactive molecules by targeting transcription factor FXR, representing an additional mechanism for bile acids effects on cardiovascular function (175).…”
Section: Secondary Bile Acidsmentioning
confidence: 99%
“…Altogether, these data show that bile acids are involved in CVD progression and in ethanol-induced gut microbiota alterations. In this context, a link between cholestasis and cardiovascular dysfunction has been proposed (175). Ethanol consumption leads to cholestasis (114,172,173,176), characterized by increased bile salt retention (176).…”
Section: Secondary Bile Acidsmentioning
confidence: 99%
“…Analogous to miRNAs, piRNAs are stable in biofluids such as plasma and blood [ 170 ]. piRNAs isolated from these biofluids were found to be deregulated in patients with colorectal cancer, prostate cancer, and pancreatic cancer [ 171 ]. More studies confirming the prognostic potential of circulating piRNAs may add a new dimension to the existing roles of piRNAs.…”
Section: Piwi-interacting Rnas (Pirnas)mentioning
confidence: 99%